2022
DOI: 10.1002/pchj.599
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth levels of healthcare workers in two periods with different intensities of COVID‐19 pandemic

Abstract: The COVID‐19 pandemic threatens health‐care workers' (HCW) mental health and well‐being. Although traumatic life events may result in psychiatric disorders, occasionally they give rise to positive changes, such as post‐traumatic growth. Accordingly, the present study evaluated the traumatic stress, anxiety, and depression levels of HCWs and their post‐traumatic growth levels during the pandemic. In addition, the study aimed to assess the changes in psychological outcomes during the pandemic. For this aim, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
(90 reference statements)
0
5
0
Order By: Relevance
“… A longitudinal study: two-time points America 213 members of the multicenter radiation department PTGI A fair-to-moderate degree of PTG was observed in personal and interpersonal relationship factors whereas the least growth was noted in spiritual and religious beliefs. Yılmaz-Karaman et al [ 24 ] Evaluate the traumatic stress, anxiety, and depression levels of HCWs and their PTG levels during the pandemic. A longitudinal study: two-time points Turkey 66 HCWs cared for patients with COVID-19 PTGI 1) No significant differences appeared between the baseline scores and 6-month follow-up in the depression, anxiety, and traumatic stress levels of HCWs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… A longitudinal study: two-time points America 213 members of the multicenter radiation department PTGI A fair-to-moderate degree of PTG was observed in personal and interpersonal relationship factors whereas the least growth was noted in spiritual and religious beliefs. Yılmaz-Karaman et al [ 24 ] Evaluate the traumatic stress, anxiety, and depression levels of HCWs and their PTG levels during the pandemic. A longitudinal study: two-time points Turkey 66 HCWs cared for patients with COVID-19 PTGI 1) No significant differences appeared between the baseline scores and 6-month follow-up in the depression, anxiety, and traumatic stress levels of HCWs.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies included in this review used it as a measurement [ 25 , 55 ]. PTG levels reached moderate and above with mean item scores of PTGI > 3 or total scores > 60 in two studies [ 24 , 38 ]. However, another study indicates that people who scored higher than the 60th percentile might have grown [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that nurses had higher depression, anxiety and post-traumatic stress symptoms in a meaningful level compared to the normal population (Muz & Erdoğan Yüce, 2021 ). In the studies, mental health problems that are assumed to be related to the professional activities of health workers such as post-traumatic stress disorder, anxiety, depression and burnout were reported during the pandemics and in the years after (Ata et al, 2023 ; Yılmaz Karaman & Yastıbaş, 2021 ; Yılmaz Karaman et al, 2023 ). Some studies in the literature that found that long-term separation of individuals from their relatives due to the absence of contamination to their immediate environment causes burnout (Baltacı, & Coşar, 2020 ; Greenberg, 2020 ).…”
Section: Introductionmentioning
confidence: 99%